Advancing Fashion Design Education: Evaluating the Eligibility of Video Tutorial Media for Basic Pattern Content in Vocational High School - Wati, Widya Rahma; Sariyatun; Sudiyanto (LPPM Undiksha, 2024)
Technological innovation should be optimally applied to all subjects, without exception art and design education in SMK. The presence of technology and learning media there should also not only improve learning methods but also make people easier to get information. This research aims to create a technological innovation in the form of Video Tutorials for learning Drawing Patterns for vocational high school students. This research is a type of research and development (R&D) by adopting 7 steps from 10 steps proposed by Borg & Gall. The subjects involved in this research consisted of 2 media experts, 2 material experts, and 3 teachers. The data collection techniques were non-test, namely interviews, observations and questionnaires. The research instruments used were a list of questions, an observation sheet and a video media feasibility questionnaire. The collected data were analyzed by finding the average, then described in paragraph form to provide an overview of the field findings and media feasibility. The results showed that the average acquisition of media experts I, II, II respectively received the Good category. As for the results of the practitioner's assessment, the average score obtained by teachers I and II consecutively fell into the Good category. Thus, video tutorial media for learning to draw patterns is declared feasible to use as learning media. The research findings successfully show that video tutorials empower students to learn independently and improve their pattern making skills, as well as enable teachers to deliver visually appealing learning, thus encouraging better information absorption among students.